Polymorphism of the LIG3 gene in keratoconus and Fuchs endothelial corneal dystrophy - Synowiec, E; Wojcik, K A; Izdebska, J; Binczyk, E; Szaflik, J; Blasiak, J; Szaflik, J P (Cellular and Molecular Biology, 2015)
The product of the LIG3 gene encodes DNA ligase III, which is involved in the repair of oxidatively damaged DNA in the base excision repair pathway. We hypothesized that polymorphism in this gene may change susceptibility to oxidative stress and predispose individuals to the development of keratoconus (KC) and Fuchs endothelial corneal dystrophy (FECD). Therefore, we investigated the association between genotypes and haplotypes of the g.29661G>A polymorphism (rs1003918) and the g.29059C>T polymorphism (rs1052536) of the LIG3 gene and the occurrence of KC and FECD in patients with FECD (258 individuals) or KC (283) and ethnically matched controls (300). The A/A genotype and the A allele of the g.29661G>A polymorphism were associated with increased occurrence of KC, while the G allele of this polymorphism was positively correlated with a decreased occurrence of this disease. The T/C genotype of the g.29059C>T polymorphism was associated with decreased FECD occurrence. In addition, the AT haplotype was associated with increased occurrence of KC and FECD, while the GT haplotype was associated with decreased occurrence of these diseases. The g.29661G>A and g.29059C>T polymorphisms may play a role in the KC and FECD pathogenesis and can be considered as markers in these diseases.